Time perception and enjoyment of professional soccer players in different training sessions: implications for assessment of session-RPE and training load - Edwards, A. M.; Coleman, D.; Fuller, J.; Kesisoglou, A.; Menting, S. G. P. (The Journal of Strength and Conditioning Research, 2024)
The purpose of this study was to investigate whether the perception of time and enjoyment levels among professional soccer players varied according to the type of training undertaken and whether this influenced the training load (TL) assessment method of session-rating of perceived exertion (sRPE). Sixteen male professional soccer players participated in this study. A diverse range of 7 training events was sampled, comprising passive sessions (e.g., long and short video analysis sessions; VA1 & VA2), sport-specific game play (small-sided games), physical tactical sessions (tactical formation training), individual skills training, and cardiovascular training sessions (long and short; CV1 & CV2). Sessions varied in duration. Subjects estimated duration, enjoyment, and perceived exertion. The activities rated as most enjoyable (all physical training sessions with the exception of CV1 & CV2) were also the sessions considered to last shortest, or time perceived as running fastest (P < 0.01). Long-duration video analysis (VA2) and high-intensity cardiovascular training (without a ball) (CV2) were rated least enjoyable (P < 0.01) and were the sessions where time estimates were longer than chronological time, indicating time perceived as running slow (P < 0.01). Differences in subjective and chronological estimates of sRPE substantially impacted TL estimates across the 5 physically active sessions (P < 0.01). The outcomes of this study indicate that systematic and task-specific variations in time perception and enjoyment exist among professional soccer players. This could be impactful for training design, optimizing the training experience, and reliably assessing TL.